2000
DOI: 10.1159/000012383
|View full text |Cite
|
Sign up to set email alerts
|

Depression but Not Anxiety Is a Significant Predictor of Physicians’ Assessments of Medical Status in Physically Ill Patients

Abstract: Background: In a cross-sectional study we investigated associations between self-ratings of anxiety and depression, physical factors and physicians’ assessments of patients’ medical status. Methods: Hospital inpatients (n = 574) consecutively admitted to internal medical wards were evaluated for the presence of anxiety and depressive symptoms using the Hospital Anxiety and Depression Scale (HADS). Physicians were asked for their perception of psychiatric problems in their patients and for their assessments of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
1
5

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 35 publications
3
19
1
5
Order By: Relevance
“…Finally, we found that among individuals with one or more past-year physical disorders, co-occurrence of anxiety disorders was associated with a higher likelihood of disability and past 30-day role impairment after adjusting for the effects of comorbid mental disorders and severity of pain. These findings are inconsistent with previous smaller studies that did not find an association between anxiety and severity of physical illness [Meyer et al, 2000]. Further replication of the current-study's findings is required.…”
Section: Discussioncontrasting
confidence: 99%
“…Finally, we found that among individuals with one or more past-year physical disorders, co-occurrence of anxiety disorders was associated with a higher likelihood of disability and past 30-day role impairment after adjusting for the effects of comorbid mental disorders and severity of pain. These findings are inconsistent with previous smaller studies that did not find an association between anxiety and severity of physical illness [Meyer et al, 2000]. Further replication of the current-study's findings is required.…”
Section: Discussioncontrasting
confidence: 99%
“…This finding is consistent with those of our previous study [14] but inconsistent with those of other studies emphasizing the importance of depression in the reporting of somatic symptoms [35,36,37]. These inconsistent results may be attributable to the possibility that relatively more anxious patients with somatic symptoms than depressed patients with somatic symptoms might have been inclined to participate in the CBT intervention used in the present study.…”
Section: Discussionsupporting
confidence: 76%
“…The majority may manifest mild symptoms of anxiety due to apprehension and vigilance related to the perceived threat from the illness and the uncertainties regarding its etiology, prognosis and outcome. Others may develop depression generally of moderate severity [24]. However, some patients may exhibit serious psychiatric symptoms necessitating psychiatric intervention.…”
Section: Discussionmentioning
confidence: 99%